Home ownership and monetary policy transmission - Winfried Koeniger; Marc-Antoine Ramelet (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We present empirical evidence on the heterogeneity in monetary policy transmission across countries with different home ownership rates. We use household-level data together with shocks to the policy rate identified from high-frequency data. We find that housing tenure reacts more strongly to unexpected changes in the policy rate in Germany and Switzerland - the OECD countries with the lowest home ownership rates - compared with existing evidence for the U.S. An unexpected decrease in the policy rate by 25 basis points increases the home ownership rate by 0.8 percentage points in Germany and by 0.6 percentage points in Switzerland. The response of non-housing consumption in Switzerland is less heterogeneous across renters and mortgagors, and has a different pattern across age groups than in the U.S. We discuss economic explanations for these findings and implications for monetary policy.
urn:nbn:de:hebis:30:3-480529
Keywords: E21; E52; R21; 330; Monetary policy transmission; Home ownership; Housing tenure; Consumption